Legal Review of the Evidence System in Handling the Criminal Act of Ordinary Theft - Manullang, Dasdo Parlindungan; Ismaidar, Ismaidar; Ramayanti, Ramayanti (Journal of Research in Social Science and Humanities, 2025)
That theft is stated in Article 362 of the Criminal Code that "Anyone who takes something, which belongs wholly or partly to another person, with the intention of possessing it unlawfully, is threatened with theft, with a maximum prison sentence of five years or a maximum fine of nine hundred rupiah . This research is normative law, namely research that refers to legal norms contained in laws and regulations, literature, legal norms that exist in society and data obtained are then analyzed to answer the problems in this research. The research is straightforward to analyze the application of land laws, the type of research used is qualitative research, namely research that is carried out by examining library materials in the field of law and laws and regulations related to the problem. Legal Review of the Evidence System in Handling Ordinary Theft Crimes . One of the objectives of issuing Perma No. 2 of 2012 is to make the criminal fines more effective. The regulation of the crime of theft both in the Criminal Code and in the 2012 Draft Criminal Code, all regulate the issue of criminal fines which are threatened either cumulatively or alternatively with imprisonment, therefore in this sub-chapter discusses the suitability of criminal punishment (especially criminal fines) with the purpose of punishment in law enforcement against the crime of petty theft. Police obstacles in handling the crime of theft are internal and external constraints, lack of evidence and witnesses, witnesses who are also needed to obtain information related to a criminal act of theft are lacking or even non-existent There is an operational budget in the field which has been very low and carries out special operations against perpetrators of theft and makes arrests of perpetrators who are proven to be caught red-handed committing the crime of theft